Pemanfaatan Media Sosial dalam Pemasaran Produk UMKM di Kelurahan Sidokumpul, Kabupaten Gresik - Zainal Abidin Achmad; Thareq Zendo Azhari; Wildan Naufal Esfandiar; Nafila Nuryaningrum; Anisah Farah Dhilah Syifana; Indah Cahyaningrum (Program Studi Ilmu Komunikasi Fakultas Dakwah dan Komunikasi, UIN Sunan Ampel Surabaya, 2020)
This research discusses how the use of social media in marketing UMKM products in Sidokumpul Village, Gresik District, Gresik Regency. The research objective is to introduce UMKM products to the wider community in order to get a bigger market potential. This research method is qualitative by using phenomenological approach. The research result is, the use of social media provides good prospects for increasing the sales of UMKM products in Sidokumpul Village, Gresik District, Gresik Regency which is experiencing the impact of the COVID-19 pandemic. This is because the digital marketing system provides an online buying and selling platform, in order to facilitate the ordering and purchasing process. So that buyers can interact with UMKM owners to make transactions directly